How to support EV adoption: Tradeoffs between charging infrastructure investments and vehicle subsidies in California. (June 2022) - Ledna, Catherine; Muratori, Matteo; Brooker, Aaron; Wood, Eric; Greene, David
Abstract: Supporting the adoption of zero-emission vehicle (ZEVs), including plug-in electric vehicles (EVs), has become a priority for governments due to their ability to reduce petroleum demand, improve air quality, and reduce carbon dioxide (CO2 ) emissions. Optimal strategies to accelerate EV adoption must weigh the relative value of alternative policy mechanisms to consumers, including public charging infrastructure and vehicle purchase subsidies. We use a historically validated light-duty vehicle consumer choice tool, the ADOPT model, to simulate personal light-duty vehicle adoption and related emissions in California. ADOPT is updated to incorporate a quantification of the tangible value of public charging infrastructure, allowing us to simulate the impact of investments in public charging infrastructure and vehicle purchase subsidies under different scenarios. We show that both policies result in increased EV adoption, with the most effective policy varying depending on vehicle technology assumptions. Under conservative technology improvement assumptions, infrastructure investments are most effective in promoting EV sales and reducing CO2 emissions, while under optimistic technology improvement assumptions a combination of infrastructure and subsidies best supports EV sales and CO2 emission reductions. Highlights: We model the impact of public charging infrastructure and subsidies on EV adoption. All policies explored support EV adoption and reduce CO2 emissions independently. Technology assumptions impact the relative effectiveness of each policy. Infrastructure is most effective in promoting BEV sales and reducing CO2 emissions under conservative technology assumptions. A combination of infrastructure and subsidies is most effective under optimistic technology assumptions.